The international covenant on economic social and cultural rights: a critical examination of the relative importance of resource constraints on benchmarks and benchmarking processes in the African context - Jackson, Laurie-Ann (Department of Public Law, 2026)
Ripping away colonial ties and bursting into an era of independence, freedom and development, African states welcomed the international movement for the development of a global human rights system in the 1950s and 60s. The pillars of this system ushered in rights that, it was hoped, would fully sever the stronghold of colonialism over African economies, cultures and governments.1 Accession, ratification, and translation of the instruments defining this system meant for millions of Africans the right to education, to vote, to self determination, to culture, and to development. Thus, with the terror and after effects of colonial subjugation, poverty, oppression and gross underdevelopment in the not so distant past, many African states signed on to the hope of their enablement to create non-discriminatory, fair, just, equitable and prosperous societies.2 Today, forty years into the creation of this hope, the continent is only thirteen years removed from the horror of the Rwandan genocide and the fall of the dehumanizing apartheid regime. Situations in Sudan, Zimbabwe, the Democratic Republic of the Congo and Swaziland are but a few of the current crises that characterize and testify to the consistent singing of this hope in Africa.